2013
DOI: 10.1148/radiol.13121637
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Hepatocellular Carcinoma: MR Imaging after Intraarterial Therapy. Part II. Response Stratification Using Volumetric Functional Criteria after Intraarterial Therapy

Abstract: Volumetric functional MR response 3-4 weeks after initial intraarterial therapy showed improved OS. Volumetric functional MR was superior to current imaging (RECIST, mRECIST, and EASL) and biochemical (AFP level) response criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 40 publications
2
29
1
Order By: Relevance
“…Furthermore, it has been shown that volumetric analysis of CT perfusion values reflects tumor heterogeneity more accurately than measurements in 2D ROIs [12]. Recent studies found that volumetric analysis of contrast-enhanced or functional MR was superior for treatment response prediction and early response assessment of HCC as opposed to two-dimensional measurements [15,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that volumetric analysis of CT perfusion values reflects tumor heterogeneity more accurately than measurements in 2D ROIs [12]. Recent studies found that volumetric analysis of contrast-enhanced or functional MR was superior for treatment response prediction and early response assessment of HCC as opposed to two-dimensional measurements [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with complete or partial target response were classified as responders, and patients with stable or progressive disease were classified as non-responders, as previously described [28].…”
Section: Evaluation Of Response To Tarementioning
confidence: 99%
“…On the contrary, anatomic metrics did not show any significant change in the responders or non-responders after therapy. Our results suggest that these potential novel functional MRI techniques can stratify patients as responders and non-responders early (1 month) after TARE, even before changes in tumor size and/or morphologic characteristics occur [16,25].…”
Section: Discussionmentioning
confidence: 77%
“…Importantly, volumetric techniques were shown to have a strong influence on how tumor response is classified and in some studies, the classification of patients as responders or nonresponders was shown to differ between 3D and non-3D techniques in up to one-third of the analyzed cases (12,13). Furthermore, 3D quantitative techniques have been repeatedly shown as beneficial in identifying tumor response more accurately, primarily because they include the whole tumor tissue into the analysis (14,15) . For assessment of radiological response after TACE, 3D volumetric measurement has a strong clinical impact to be able to accurately measure what part of the lesion is necrotic and viable(16).…”
Section: Discussionmentioning
confidence: 99%